2018
DOI: 10.1186/s12879-018-3191-9
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of hepatitis B vaccination and its determinants among health care workers in a tertiary health facility in Enugu, South-East, Nigeria

Abstract: BackgroundHepatitis B vaccination is the most effective method of prevention for hepatitis B virus infection. It is a major public health problem in Nigeria, and health workers are at increased risk. This study determined the uptake of hepatitis B vaccination and assessed its determinants among health care workers (HCWs).MethodsA hospital-based cross-sectional study was conducted between July and August, 2016 using self-administered structured questionnaires among 3132 HCWs in University of Nigeria Teaching Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
47
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 16 publications
(20 reference statements)
15
47
4
1
Order By: Relevance
“…However, we found that a lower number of students (43.2%) were aware of the recommended number of doses of the vaccine despite knowing the correct route of administration (75.3%).Our findings are similar to those among medical students in Cameroon that showed a majority had adequate knowledge of HBV infection and vaccine, and HBV transmission [31]. However, they are different from those found among medical students in India, Syria, Nigeria and Lao PDR, which found poor knowledge, and lack of awareness about hepatitis B, its routes of transmission, risk factors, and modes of prevention [32][33][34][35].…”
Section: Discussionsupporting
confidence: 74%
“…However, we found that a lower number of students (43.2%) were aware of the recommended number of doses of the vaccine despite knowing the correct route of administration (75.3%).Our findings are similar to those among medical students in Cameroon that showed a majority had adequate knowledge of HBV infection and vaccine, and HBV transmission [31]. However, they are different from those found among medical students in India, Syria, Nigeria and Lao PDR, which found poor knowledge, and lack of awareness about hepatitis B, its routes of transmission, risk factors, and modes of prevention [32][33][34][35].…”
Section: Discussionsupporting
confidence: 74%
“…Fourteen included studies assessed the awareness of 9,446 Africans in regard to HBV, three studies were conducted in each of Nigeria [61,62,64] , Cameroon [20,40,58] and Ghana [12,15,28] , two in Ethiopia [32,52] , one in each of Kenya, Mozambique and Madagascar [26,57,71] . The oldest among the study included was conducted in 2010 while the newest was conducted in 2016 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen included studies assessed the awareness of 9,446 Africans in regard to HBV, three studies were conducted in each of Nigeria [61,62,64], Cameroon [20,40,58] and Ghana [12,15,28], two in Ethiopia [32,52], one in each of Kenya, Mozambique and Madagascar [26,57,71]. The oldest among the study included was conducted in 2010 while the newest was conducted in 2016 (Table 1).…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%